2015
DOI: 10.1103/physreve.91.041001
|View full text |Cite
|
Sign up to set email alerts
|

Generation of magnetic fields by large-scale vortices in rotating convection

Abstract: We propose a self-consistent dynamo mechanism for the generation of large-scale magnetic fields in natural objects. Recent computational studies have described the formation of large-scale vortices in rotating turbulent convection. Here we demonstrate that for magnetic Reynolds numbers below the threshold for small-scale dynamo action, such turbulent flows can sustain large-scale magnetic fields, i.e., fields with a significant component on the scale of the system.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 24 publications
1
64
0
Order By: Relevance
“…The friction coefficient f r , which, in the case of Ekman pumping, stands for the ratio L=h, is left here as a parameter to control the relative importance of the geostrophic modes in the saturated flow. We expect other mechanisms of specific dissipation (see, e.g., magnetic [15,43], quadratic, scale dependant) to lead to similar results. The simulations hereafter are carried out with f r ¼ 10 −2 and f r ¼ 1.…”
Section: -2mentioning
confidence: 53%
See 2 more Smart Citations
“…The friction coefficient f r , which, in the case of Ekman pumping, stands for the ratio L=h, is left here as a parameter to control the relative importance of the geostrophic modes in the saturated flow. We expect other mechanisms of specific dissipation (see, e.g., magnetic [15,43], quadratic, scale dependant) to lead to similar results. The simulations hereafter are carried out with f r ¼ 10 −2 and f r ¼ 1.…”
Section: -2mentioning
confidence: 53%
“…The same issue arises in twodimensional turbulence, where it is solved adding largescale friction [49]. Lastly, additional physics, such as imposing a background magnetic field [15,43], can also be responsible for precluding the emergence of large-scale geostrophic flows. The friction coefficient f r , which, in the case of Ekman pumping, stands for the ratio L=h, is left here as a parameter to control the relative importance of the geostrophic modes in the saturated flow.…”
Section: -2mentioning
confidence: 99%
See 1 more Smart Citation
“…Tilgner [63,64] found a transition from the mean field dynamo mechanism of Childress and Soward [15] to a dynamo of fluctuation-type. The recent work of Guervilly et al [28] examined the influence of the inverse cascade and associated large-scale vortex on the resulting dynamo; they found that for P m 1, the mean magnetic field is weak and the inverse cascade is less pronounced, in comparison to a case at P m = 0.2 where a significant inverse cascade and mean magnetic field are present. It should be noted that all of these investigations, despite the advantage of being in a computationally simple plane layer, are at parameters well away from those relevant to planetary interiors.…”
Section: Introductionmentioning
confidence: 99%
“…The flow may then act as a dynamo, as a consequence of which the strong small-scale magnetic field diminishes the coherence of the Reynolds stresses, and hence the driving for the large-scale vortices. Whether this signifies the demise of the large-scale vortices, or whether they can recover, depends critically on the value of Rm, which determines whether the small-scale field can be maintained (Guervilly et al 2015). Although the physics is more complicated than that considered in this paper, in that the magnetic field is selfgenerated rather than imposed, the main underlying idea is again that a strong small-scale field can inhibit turbulent transport.…”
Section: Discussionmentioning
confidence: 88%